ANALISIS KINERJA KEUANGAN PEMERINTAH KOTA GORONTALO DALAM PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH TAHUN 2019-2023 - Larasati, Cindy; Ali, Yuwin; Ariesta Iyonu, Mentari (Universitas Muhammadiyah Bengkulu, 2025)
This study aims to analyze the financial performance of the Gorontalo City Government in the 2019–2023 period using a mixed methods sequential explanatory model approach. Quantitative data were obtained from the City Budget Realization Report (LRA), balance sheet, and CAKL, analyzed using seven financial ratios: independence, degree of decentralization, dependence, PAD effectiveness, efficiency, spending activity, and PAD growth. The qualitative stage involved semi-structured interviews with informants from the City Finance Agency and taxpayers. The results showed that the average independence ratio was 40.87% (low category), the degree of decentralization was 25.97% (sufficient), financial dependence was 64.29% (very high), and PAD effectiveness was sufficient (94.34%), but efficiency decreased (104.65%) and operating expenses dominated (87.72%) compared to capital expenditures (11.99%). PAD growth fluctuated with a low average (15.35%). Qualitative analysis revealed the main factors: suboptimal financial management, low PAD due to tax and policy awareness, and a small portion of capital expenditure. In conclusion, the financial performance of Gorontalo City is not yet independent and efficient, still highly dependent on central transfers, needs to improve management, increase PAD, and increase the portion of capital expenditure to strengthen fiscal independence and regional development. Keywords: Financial Performance, Regional Financial, Independence Ratio